2002
DOI: 10.1034/j.1600-0838.2002.120206.x
|View full text |Cite
|
Sign up to set email alerts
|

Walking trials in postmenopausal women: effect of one vs two daily bouts on aerobic fitness

Abstract: We compared the effects of one vs two daily bouts of walking on aerobic fitness and body composition in postmenopausal women. One hundred and thirty-four subjects were randomized into exercise groups or a control group and 130 completed the study. The subjects walked 5 d/week for 15 weeks at 65% of their maximal aerobic power expending 300 kcal (1255 kJ) in exercise in one (Group S1) or two daily sessions (Group S2). VO(2max) was measured in a direct maximal treadmill test. Body mass index (BMI) was calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(87 citation statements)
references
References 22 publications
4
81
1
1
Order By: Relevance
“…The exercise training in group E2 was fractionated into 2 daily bouts, and control group subjects (group C) kept their daily physical activity habits unchanged. We have previously reported that both of these training regimens improvedVo 2 max, measures of submaximal fitness, resting blood pressure, body mass, the proportion of body fat 16 as well as blood lipids and glucose and insulin levels. 17 The main outcome measures were lowerextremity muscle strength, balance, and walking performance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exercise training in group E2 was fractionated into 2 daily bouts, and control group subjects (group C) kept their daily physical activity habits unchanged. We have previously reported that both of these training regimens improvedVo 2 max, measures of submaximal fitness, resting blood pressure, body mass, the proportion of body fat 16 as well as blood lipids and glucose and insulin levels. 17 The main outcome measures were lowerextremity muscle strength, balance, and walking performance.…”
Section: Methodsmentioning
confidence: 99%
“…As described in a previous publication, 16 the main outcome was directly measuredVo 2 max. The calculations for adequate sample size were based on the assumption of an approximately 10% (3 mL⅐min Ϫ1 ⅐kg Ϫ1 [SDϭ4]) increase from the baselineVo 2 max in the exercise group when compared with the change in the control group (type 1 error alphaϭ.05).…”
Section: Sample Size and Statistical Analysesmentioning
confidence: 99%
“…Much research concerning walking interventions has assessed the effects of training typically 4 or 5 days per week for 30-60 min [7,[9][10][11][12][13][14][15][16][17]. However, to the authors' knowledge, only one study has examined the efficacy of walking at the minimum ACSM * recommendations, that is, 20 min on 3 days of the week [18].…”
Section: Introductionmentioning
confidence: 99%
“…Five to ten minutes might be suffi cient. Reviews from Blair & Connelly (1996), Shephard (1997) or Hardman (1999) and Hardman (2001) and studies of walking (Asikainen et al 2002b;Murphy et al 2002;OseiTutu & Campagna 2005) came up with further evidence with regard to physiological functioning and fi tness-related outcomes. Here, two randomised trials of accumulated daily stair climbing are remarkable (one ascent takes 2 min!).…”
Section: Measurement Of Pamentioning
confidence: 99%